The economics of the Middle East and North Africa (MENA) - Pelzman, Joseph (World Scientific Pub., 2019)
The Middle East and North Africa (MENA) is a large, complex, and diverse region, which faces a wide range of economic issues. The purpose of this book is not to provide a country-by-country study but rather to deal with general themes found in Arab MENA and Israel, such as problems associated with growth and structural change; the role of State-intervention and the development of oligarchies in country-specific local markets; labor market imperfections driven by gender bias; technology gaps and endogenous growth; capital market development in a restricted financial model based on religious constraints; savings and investment behavior in a model of state subsidization and intervention designed to control local development; and the role of the state in inducing bottom-up corruption. Data sources used in the volume include country-specific data, World Bank, UN, IMF and OECD.